BAGAIMANA REAKSI PASAR TERHADAP PERISTIWA AMANDEMEN AKUNTANSI IMBALAN KERJA - Rahmi Izzati Putri; Iman Haymawan (Universitas Katolik Indonesia Atma Jaya, 2021)
The purpose of this study is to see the market reaction before and after the event of the work imbalance accounting amendment ratification. This study uses a total of 311 observations of companies listed on the Indonesia Stock Exchange (IDX) during 2013 and uses the Event Study research approach and Paired Sample T-test analysis techniques to test differences in market reactions as indicated by Cumulative Abnormal Return (CAR) before and after. event ratification of the work imbalance accounting amendment. This study found that there was a positive and significant difference in CAR between before and after the event of ratification of the work imbalance accounting amendment. This research has implications for investors to get a picture of the market reaction that occurs as a result of the ratification of the work imbalance accounting amendment. The results of this study indicate that there are differences in market reactions between prior to the ratification of the work imbalance accounting amendment